2020
DOI: 10.1101/2020.02.13.948596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct regionalization patterns of cortical morphology are associated with cognitive performance across different domains

Abstract: Cognitive performance in children is predictive of academic and social outcomes; therefore, understanding neurobiological mechanisms underlying individual differences in cognition during development may be important for improving outcomes. Some theories of intelligence argue that a single latent, psychological construct with a specific neural substrate underlies many cognitive processes. In a previous study, we showed that a distributed configuration of cortical surface area and apparent thickness was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 98 publications
1
9
0
Order By: Relevance
“…One of the strengths of our approach is the assessment of how performance in different cognitive domains associates with a wide range of brain measurements. Overall, our results show that effect sizes tend to be moderate (at most explaining less than 10% of the variance after stacking), which nevertheless go in line with a recent research in a large sample size (N = 10,145) reporting a similar degree of variability using cortical morphology information for predicting fluid and crystallized intelligence [30]. Likewise, we adopted a rigorous strategy that takes in consideration the effects of factors that are known to confound predictions of individual differences in behaviour and cognition (e.g., brain size and education level).…”
Section: Discussionsupporting
confidence: 91%
“…One of the strengths of our approach is the assessment of how performance in different cognitive domains associates with a wide range of brain measurements. Overall, our results show that effect sizes tend to be moderate (at most explaining less than 10% of the variance after stacking), which nevertheless go in line with a recent research in a large sample size (N = 10,145) reporting a similar degree of variability using cortical morphology information for predicting fluid and crystallized intelligence [30]. Likewise, we adopted a rigorous strategy that takes in consideration the effects of factors that are known to confound predictions of individual differences in behaviour and cognition (e.g., brain size and education level).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, female CAN users had more robust correlations between volume and neuropsychological performance in left inferior temporal and right superior frontal regions. However, it is notable that the smallest sample size was of female CAN users; thus, these findings need replication in larger samples as the magnitude of brain–behavior relationships is potentially smaller than previously recognized (Palmer et al, 2020). Importantly, previous research has demonstrated neuropsychological differences prior to CAN initiation, which represent a risk for use (Cheetham et al, 2012; Jackson et al, 2016; Tervo-Clemmens, Quach, Calabro, Foran, & Luna, 2020), and thus the present findings—particularly the preliminary brain–behavior relationships—are noted as associations rather than causal relationships.…”
Section: Discussionmentioning
confidence: 85%
“…The extent to which we can associate TPVT and PERT with high-level naturalistic language and ToM is an open area of investigation ( Chen et al, 2019 ; Oakley et al, 2016 ). However, multiple neuroimaging studies have used TPVT and PERT-like assessments to understand the broader networks of language and ToM ( Chen et al, 2019 ; Hawco et al, 2017 ; JĂĄni and KaĆĄpĂĄrek, 2018 ; Mier et al, 2010 ; Palmer et al, 2020 ). In addition, awake intraoperative neurosurgical mapping of language and ToM have utilized similar assessments in the operating room in an effort to preserve the cognition of their patients.…”
Section: Discussionmentioning
confidence: 99%